2021
DOI: 10.1155/2021/5589829
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance with Transformers: A Framework to Detect Adverse Drug Reactions Using BERT Fine-Tuned with FARM

Abstract: Adverse drug reactions (ADRs) are the undesirable effects associated with the use of a drug due to some pharmacological action of the drug. During the last few years, social media has become a popular platform where people discuss their health problems and, therefore, has become a popular source to share information related to ADR in the natural language. This paper presents an end-to-end system for modelling ADR detection from the given text by fine-tuning BERT with a highly modular Framework for Adapting Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Tweets are more difficult to classify due to their characteristics: They are limited to 280 characters but can be much shorter; they are not necessarily written with correct syntax; and they can contain abbreviations, misspellings, and slang words [ 44 ]. We also observed that the results of predictions are generally significantly better for correctly written texts such as PubMed abstracts, than with tweets, for example [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tweets are more difficult to classify due to their characteristics: They are limited to 280 characters but can be much shorter; they are not necessarily written with correct syntax; and they can contain abbreviations, misspellings, and slang words [ 44 ]. We also observed that the results of predictions are generally significantly better for correctly written texts such as PubMed abstracts, than with tweets, for example [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that data science is an empirical discipline in which only experiments make it possible to determine the most appropriate approach in a defined context and that there is no method that makes it possible to confidently improve the results. In some cases, multitask learning made it possible to improve the results [ 45 , 62 , 63 ]. However, previous studies, such as that by Rodriguez et al [ 64 ], observed that multitask learning did not improve the results in general.…”
Section: Discussionmentioning
confidence: 99%
“…[30] used contextual information in extracting long distance adverse drug events from clinical notes with BERT models. There were also overlaps between domains, such as work that introduced a system for detecting adverse drug reactions from text on social media by fine-tuning BERT [31].…”
Section: Resultsmentioning
confidence: 99%
“…Weight loss seems more difficult to classify and can be confused with weight gain - perhaps because these two classes share very similar syntactic elements. If an expert review of identified signals will likely remain essential for assessing a drug’s causality in the occurrence of adverse effects, it will be interesting to investigate how these models can aid in contextualizing the findings to support causality determination (47). Because online comments are often written with little contextual information, it is difficult to establish a causal relationship between drug use and the occurrence of an event.…”
Section: Discussionmentioning
confidence: 99%